THE RELATIONSHIPS AMONG LECTURERS’ SELF-CONCEPT AND LEADERSHIP STYLE AND STUDENTS’ MOTIVATION TO LEARN ENGLISH AT TERTIARY LEVELS OF EDUCATION - Dwi Maharrani (Universitas Indo Global Mandiri, 2017)
This study was aimed to find out (a) the existing phenomena of English lecturers’ of non-English major self-concept and leadership style at Sriwijaya University, (b) the existing phenomena of non-English major students’ motivation to learn English at Sriwijaya University, (c) whether or not there was significant correlation among lecturers’ self-concept and leadership style and students’ motivation to learn English, (d) how much lecturers’ self-concept and leadership contribute to students’ motivation to learn English. The data were collected by distributing self-concept questionnaire and leadership questionnaire to 19 English teachers of non-English majors and motivation to learn English questionnaire to 714 non-English major students. The result described that the lecturers’ self-concept was mostly positive for the five sub-scales with the highest positive percentage was for self-regard (84.9%). For the leadership style, the result revealed that 10.5 % of the lecturers had country club leadership style and the other 89.5% had team leader leadership style. In terms of students’ motivation to learn English, the twelve subscales were dominantly responded positively by the students with the highest percentage (96.5%) went to integrative orientation subscale. Furthermore, there was significant correlation between lecturers’ self-concept (total) and students’ motivation to learn English (total) (R2= .006, sig. F= .044). However, there is no significant correlation between lecturers’ leadership style and students’ motivation to learn English. Key words: lecturers’ self-concept, lecturers’ leadership styles, students’ motivation